Voices of Southeast Asia essential readings from antiquity to the present (M.E. Sharpe, 2014)
"A primary source reader featuring 24 selections from a variety of genres and designed as a resource for teaching Southeast Asian civilization courses, whether their emphasis be historical, literary, philosophical, or broadly cultural, and as a means of integrating Southeast Asian civilization into broader world history coverage ... Selections range from the Cambodian medieval version of the Ramayana to the 16th century Javanese tales to modern Thai short stories. The region is represented both temporally and geographically with selections from Cambodia, Malaysia, Thailand, Vietnam, Indonesia, Laos, Philippines, and Burma. These readings represent a fair selection of Southeast Asia's ancient and modern classics of thought and expression. This volume constitutes a unique combination of poetry, novels, short stories, drama, and political and philosophical treatises. Although not every selection is a complete work, the material presented is both substantial and representative"--Provided by publisher.